Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, February 06, 1930 - Hawley, Joseph Roswell (The Hartford Times, Inc., 1930)
Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, February 06, 1930. Hawley was too solid and four square on fundamental principles to be anything but to. sound money man. He objected to the inflation of the currency by issuance of greenbacks lacking adequate gold reserves and he was opposed to the efforts of the silver men to compel the government to buy their product and coin silver money for the sake of supplying a market for the miners of the white metal. He objected to the banking bill before congress at its regular session in December, 79, giving national banks the options of having their reserves in either gold or silver. He was violently opposed to the resolution of Representative Price which would require reserves of both gold and silver. Representative Fort of Illinois had attempted to interpret President Hayes to congress on the money question, without any great success. When the army appropriation bill came before the house Hawley oversaw it on the republican side. On December 10, he wrote to Warner.
1 electronic record. Scanned newspaper article. 1 image scans. 897 KB (918,835 bytes). 2 PDF copies (Master: PDF/A fmt/477; Access: reduced sized PDF fmt/19). 19.6 MB (20,630,638 bytes).
Keywords: Hawley, Joseph R. (Joseph Roswell), 1826-1905; American Civil War (United States : 1861-1865); United States--History--Civil War, 1861-1865; Personal correspondence; Letters; Newspapers